Fixation of Mitchell's osteotomy with bioabsorbable pins for treatment of hallux valgus deformity. - Nikolaou, Vassilios S; Korres, Demitrios; Xypnitos, Fragiskos; Lazarettos, John; Lallos, Stergios; Sapkas, Georgios; Efstathopoulos, Nicolas (Int Orthop, 2009)
We hypothesised that the use of bioabsorbable pins in Mitchell's osteotomy would improve the outcome of patients treated for hallux valgus deformity. A total of 68 patients underwent Mitchell's osteotomy to correct hallux valgus deformity: 33 patients (group A) underwent Mitchell's osteotomy augmented with bioabsorbable pins and 35 patients were treated with the classic operative procedure (group B). Hallux valgus angle (HVA), intermetatarsal angle (IMA), the American Orthopaedic Foot and Ankle Society (AOFAS) hallux metatarsophalangeal-interphalangeal scale and the visual analogue score (VAS) for pain were measured preoperatively and postoperatively. There was no statistically significant difference between the two groups as far as the improvement of the IMA, HVA and AOFAS scale were concerned. Patients of group A had significantly less postoperative pain and returned to their previous activities earlier than patients of group B. The use of the pins did not improve the final outcome of the osteotomy. However, it allowed for faster rehabilitation due to less postoperative pain.
Keywords: Absorbable Implants; Adult; Aged; Bone Nails; Female; Hallux Valgus; Humans; Male; Metatarsal Bones; Middle Aged; Osteotomy; Pain; Pain Measurement; Postoperative Complications; Preoperative Care; Prosthesis Design; Young Adult